2005
DOI: 10.1002/bjs.5120
|View full text |Cite
|
Sign up to set email alerts
|

Screening for abdominal aortic aneurysm in a geographically isolated area

Abstract: Screening for abdominal aortic aneurysm can be carried out in a remote and rural area with high uptake, acceptable clinical results and at no greater cost than in more densely populated areas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 14 publications
0
11
0
1
Order By: Relevance
“…Abdominal Aortic Aneurysm (AAA) has a prevalence of around 5% in men who are over 65 years 1,2 and is responsible for 1.4% of deaths in men in the UK. 3 Screening men over 65 has been shown to reduce aneurysm related mortality 4e7 and to be cost effective 4,8e11 although any screening programme is dependent upon its uptake to be effective.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Abdominal Aortic Aneurysm (AAA) has a prevalence of around 5% in men who are over 65 years 1,2 and is responsible for 1.4% of deaths in men in the UK. 3 Screening men over 65 has been shown to reduce aneurysm related mortality 4e7 and to be cost effective 4,8e11 although any screening programme is dependent upon its uptake to be effective.…”
Section: Introductionmentioning
confidence: 99%
“…Screening is offered at over 50 sites across the region. The programme has previously reported high uptake 2 and the long term follow-up of men who attended for screening has been described. 14 Socioeconomic status is indicative of deprivation and has been shown to affect the uptake of screening for cancer.…”
Section: Introductionmentioning
confidence: 99%
“…AAA screening has been undertaken in the neighbouring Highland region among men aged 65–74 years since 2001. After two invitations overall uptake was 90 per cent across 51 sites (mainly general practice surgeries and a single city hospital) over 10 years.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that AAA screening programs in rural or underserved areas can be successful and cost-effective. 20,21 By preventing the rupture before it happens, any discussion about difference in mortality by surgeon specialization becomes moot.…”
Section: Discussionmentioning
confidence: 99%